DALY trend and predictive analysis of COPD in China and its provinces: Findings from the global burden of disease study - Zhai, Mimi; Jiang, Qin; Liu, Sushun; Long, Jianhai; Zhang, Dan; Ren, Chutong; Gong, Yi; Li, Yamin (Frontiers in Public Health, 2022)
Background Chronic obstructive pulmonary disease (COPD) is the most common chronic respiratory disease in the world, especially in China. Few studies have explored the trend of COPD in China and its provinces. This study aimed to demonstrate and predict the trend of COPD DALY in China and its provinces based on the global burden of disease (GBD) data. Methods The data on COPD disability-adjusted life year (DALY) were collected from GBD 2017, GBD 2019, and the National Bureau of Statistics of China. The age-standardized rate (ASR) was used to evaluate the trend of COPD DALY by gender, age, and risk factors in China and its provinces. In addition, the trend of COPD considering the aging population in the next 10 years was also predicted. Results In China, the COPD DALY was 20.4 million in 2017, which decreased to 24.16% from 1990 to 2017. Most provinces showed a downward trend, with the exception of Taiwan which increased by 127.78%. The ASR of DALY was 1445.53 per 100,000 people in 2017 and demonstrated a significant decrease. Among all provinces, only Taiwan (97.78%) and Hubei (2.21%) demonstrated an increased trend of ASR. In addition, Tibet ranked third with a decline of 56.95%, although its ASR was the highest in 1990. Smoking and air pollution were the main risk factors for COPD and varied with regions, gender, and age. The proportion of COPD DALY attributable to smoking was higher in the middle-aged and elderly male population and did not decrease in China. Moreover, the ASR attributable to air pollution of the elderly decreased significantly in China. Socio-demographic index (SDI) and educational level were also found to be related to ASR. By predicting the ASR trend in the next 10 years, we found that the ASR attributable to smoking might increase significantly among men. The ASR attributable to air pollution showed a significant decrease in women. Unfortunately, ASR attributable to second-hand smoke was found to increase in women. Conclusion Chronic obstructive pulmonary disease is the leading contributor to the burden of global diseases. Although China and its provinces demonstrated a downward trend of COPD DALY, some provinces still faced challenges. Moreover, ASR attributable to risk factors was different in regions, gender, age, and years. The predicted trend of COPD was also different. Therefore, more targeted strategies should be formulated to reduce the burden of COPD in China and its provinces.